1992
DOI: 10.2527/1992.7041227x
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary intake and ingestive behavior of steers grazing Johnstone or endophyte-infected Kentucky-31 tall fescue

Abstract: Effects of grazing low-endophyte (Acremonium coenophialum Morgan-Jones and Gams, less than 1% infection) Johnstone (J) or high-endophyte (60% infection) Kentucky-31 (K) tall fescue (Festuca arundinacea Schreb.) on grazing behavior and voluntary intake were studied. Six Angus steers (average initial BW = 326 kg) grazed 1.21-ha plots of each forage cultivar (three steers per cultivar) in four 28-d periods beginning May 27. Daytime observations (0630 until 2130) revealed that J steers spent more (P less than .10)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Contrary t o previous reports of decreased intake of endophyte-infested hay, seed, or green-chop diets compared with LE or endophyte-free diets under thermal stress conditions (Schmidt et al, 1982;Jackson et al, 1984;Strahan et al, 19871, we observed no decrease in DM1 of HE KY-31 relative to Johnstone. Data from our study are in agreement with those from other cattle grazing studies (Howard et al, 1992;Peters et al, 1992). Hemken et al (1981) reported no differences in voluntary intake among tall fescue cultivars at moderate ambient temperatures ( 10 to 18°C).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Contrary t o previous reports of decreased intake of endophyte-infested hay, seed, or green-chop diets compared with LE or endophyte-free diets under thermal stress conditions (Schmidt et al, 1982;Jackson et al, 1984;Strahan et al, 19871, we observed no decrease in DM1 of HE KY-31 relative to Johnstone. Data from our study are in agreement with those from other cattle grazing studies (Howard et al, 1992;Peters et al, 1992). Hemken et al (1981) reported no differences in voluntary intake among tall fescue cultivars at moderate ambient temperatures ( 10 to 18°C).…”
Section: Resultssupporting
confidence: 92%
“…Forage mass ranged from 3,215 to 5,272 k g h a (data not shown) and was not expected to be limiting to DM1 or animal performance (Allden and Whittaker, 1970;Jamieson and Hodgson, 1979). The results of the present study, in conjunction with other pasture studies (Howard et al, 1992;Peters et al, 19921, suggest that previous reports of decreased voluntary intake with conserved endophyte-infested tall fescue forage under controlled environmental conditions may not be readily applicable to free-grazing cattle under pasture conditions. Forage DMD coefficients (Table 5) were not different ( P > .…”
Section: Resultsmentioning
confidence: 39%
“…This may be attributed to cattle grazing patterns with Eþ animals tending to shift their grazing time to cooler periods of the day or at night (Bond et al, 1984;Stuedemann et al, 1985), whereas E À animals graze throughout the day. Also, Eþ animals spend more time idling and standing under shade (Howard et al, 1992). Even with differences during peak hours, the relationship between T rum and T a or T bg was the same for both treatments.…”
Section: Discussionmentioning
confidence: 58%
“…Approximately 20-30% of C3 pooid grasses harbour asymptomatic and vertically transmitted fungal endophytes which may confer defences against herbivores by the synthesis of harmful alkaloids, concentrating the alkaloids in sheaths, developing inflorescences, and mature seeds (Leuchtmann 1992;Clay 1996;Schardl et al 2012;Saikkonen et al 2013;Young et al 2013). These endophytes are responsible for producing four alkaloid typesergots, lolitrem, lolines and peraminesand some of them have severe effects on animal performance, grazing behaviour or voluntary intake (Howard et al 1992;Porter & Thompson 1992;Jones et al 2000;Leuchtmann et al 2000;Schardl et al 2013).…”
Section: Introductionmentioning
confidence: 99%